Research Update: Recent progress on 2D materials beyond graphene: From ripples, defects, intercalation, and valley dynamics to straintronics and power dissipation - Zhong Lin; Yu Lei; Shruti Subramanian; Natalie Briggs; Yuanxi Wang; Chun-Li Lo; Eilam Yalon; David Lloyd; Sanfeng Wu; Kristie Koski; Richard Clark; Saptarshi Das; et al. (APL Materials, 2018)
The field of two-dimensional (2D) materials has witnessed several significant advancements in a short period of time. There have been extensive research efforts dedicated to this field and an expanding community of researchers built around the same. The focus of this review article is on the most recent milestones in several aspects of 2D materials with emphasis on transition metal dichalcogenides, such as improved synthesis and property engineering, approaching this from both experimental and theoretical viewpoints. There is also an attempt at highlighting some emerging material properties that are of interest and use of these 2D materials in several electronic applications.